(untitled) (Ustozlar uchun, 2026)
This article explores the psychological foundations of the Growth Mindset—the belief that intelligence and abilities are malleable rather than fixed—and investigates how parental and educator feedback serves as a primary architect of childhood resilience. By synthesizing the research of Carol Dweck and contemporary developmental psychologists, the piece examines the critical distinction between Person Praise (focusing on innate talent) and Process Praise (focusing on effort and strategy). The analysis reveals that while trait-based compliments often inadvertently foster a fear of failure and risk aversion, process-oriented feedback empowers children to view setbacks as essential learning opportunities. Ultimately, the article argues that by shifting our linguistic habits and embracing "the power of yet," we can equip the next generation with the cognitive flexibility and persistence required to navigate lifelong challenges.